Analisis Kontrak Keanggotaan Gym Dalam Perspektif Hukum Perlindungan Konsumen - Syarif Hidayatullah; Marjan Miharja (HUMANIORUM, 2026)
Indonesia’s fitness industry is rapidly growing as public awareness of the importance of exercise increases. However, many gyms impose unilateral standard contracts containing non-refund clauses, auto-debit systems, and strict cancellation policies. These practices often harm consumers, as seen in the sudden closure of Gold’s Gym Indonesia in 2025, which led to refund claims totaling Rp 4.4 billion. This study aims to analyze the form and content of standard clauses in fitness center membership contracts in Indonesia and evaluate their compliance with Law Number 8 of 1999 concerning Consumer Protection. Using a normative legal research method with a case study approach, this study combines empirical data on contract practices with legal material analysis. The findings indicate that unilateral standard contracts may be null and detrimental to consumers. Therefore, organizations such as YLKI and BPSK play a crucial role in dispute resolution, preventive education, and ensuring fair and transparent contract practices to protect consumer rights.uits.